Genetic group x ambient temperature interaction effects on physiological responses and growth performance of rabbits - Zeferino, C. P. [UNESP]; Moura, Ana Silvia Alves Meira Tavares [UNESP]; Fernandes, S. [UNESP]; Kanayama, J. S. [UNESP]; Scapinello, C.; Sartori, José Roberto [UNESP] (Elsevier B.V., 2011)
The objective of this study was to evaluate the effects of the interaction between genetic group (Botucatu or crossbred) and ambient temperature (thermoneutral, moderate or intense heat stress) on physiological indicators and performance of growing rabbits. Ninety-six weaned rabbits were used, half from the Botucatu genetic group and half crossbreds (New Zealand White males x Botucatu females). They were assigned to a completely randomized design in a 2 x 3 factorial arrangement (two genetic groups and three ambient temperatures) with repeated measures (weeks). Colonic temperature, skin surface temperature, ear surface temperature, and respiratory rate were recorded from 42 to 67 days of age, whereas body weight and feed intake were recorded from 35 to 70 days of age. Average ambient temperature and relative humidity in the environmental chambers were 18.4 degrees C and 63.9% (thermoneutral), 24.4 degrees C and 80.2% (moderate heat stress) and 29.6 degrees C and 75.9% (intense heat stress). Mean colonic temperatures ranged from 39.4 to 39.7 degrees C across treatments. Botucatu rabbits showed higher (P<0.05) skin surface temperature under moderate heat stress than the crossbreds (33.0 +/- 0.1 vs. 32.6 +/- 0.1 degrees C, respectively) and higher (P<0.01) respiratory rates independently of ambient temperature (161.4 +/- 2.8 vs. 148.1 +/- 2.8 breaths/min, respectively) than the crossbreds. Skin surface temperature, ear surface temperature and respiratory rate were positively related to ambient temperature. Under intense heat, average daily gain of Botucatu rabbits was higher (P<0.05) than that of the crossbreds (33.72 +/- 0.90 vs. 30.66 +/- 0.96 g/day, respectively), but there was no difference with thermoneutral or moderate heat conditions. This finding characterizes a genotype x environment interaction. When the age effect was considered, an increase in colonic temperature under intense heat was detected over the last week. Respiratory rate increased in both genetic groups from six to eight weeks of age, but the increase was more pronounced in Botucatu rabbits than in crossbreds, and the difference between groups was consistently amplified over weeks. Intense heat severely depressed average daily gain as age advanced, especially beyond week eight. As expected, feed consumption increased during the experimental period, but the rate was inversely proportional to ambient temperature. Under intense heat stress, feed consumption of Botucatu rabbits was slightly, but consistently, higher than that of the crossbreds as age advanced. Relevant differences in physiological responses and growth performance between rabbit genetic groups under heat stress were detected. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Body temperature; Feed consumption; Genetic group; Growth; Respiratory rate; Thermal neutral zone